Impaired statistical learning of non-adjacent dependencies in adolescents with specific language impairment - Hsu, Hsinjen Julie; Tomblin, J Bruce; Christiansen, Morten H. (Frontiers in Psychology, 2014)
Being able to track dependencies between syntactic elements separated by other constituents is crucial for language acquisition and processing (e.g., in subject-noun/verb agreement). Although long assumed to require language-specific machinery, research on statistical learning has suggested that domain-general mechanisms may support the acquisition of nonadjacent dependencies. In this study, we investigated whether individuals with specific language impairment (SLI)—who have problems with long-distance dependencies in language—also have problems with statistical learning of nonadjacent relations. The results confirmed this hypothesis, indicating that statistical learning may subserve the acquisition and processing of long-distance dependencies in natural language.